1974
DOI: 10.1084/jem.140.4.977
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of the Immune Response

Abstract: In vitro antigen-induced tritiated thymidine uptake has been used to study the response of sensitized lymphocytes to (T,G)-A--L, (H,G)-A--L, and (Phe,G)-A--L in responder and nonresponder strains of mice. The reaction is T-cell and macrophage dependent. Highly purified T cells (91% Thy 1.2 positive) are also responsive, suggesting that this in vitro lymphocyte transformation system is not B-cell dependent. Lymphocytes from high and low responder mice stimulated in vitro react as responders and nonresponders in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1975
1975
1981
1981

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…With this assay system, it was first established that the immune response to these antigens of restricted heterogeneity was controlled by an I-Ab region gene. As expected from previous studies [15,16] B10 mice were found to be responders to (TG)A-L and beef insulin, while B1O.A mice were nonresponders (see Table I). Since the recombinant strains BlO.A(4R) and BlO.MBR were both found to be non-responders, the proliferative responses to both (TG)A-L and beef insulin were shown to require a gene coded in the I-Ab subregion.…”
Section: Resultssupporting
confidence: 88%
“…With this assay system, it was first established that the immune response to these antigens of restricted heterogeneity was controlled by an I-Ab region gene. As expected from previous studies [15,16] B10 mice were found to be responders to (TG)A-L and beef insulin, while B1O.A mice were nonresponders (see Table I). Since the recombinant strains BlO.A(4R) and BlO.MBR were both found to be non-responders, the proliferative responses to both (TG)A-L and beef insulin were shown to require a gene coded in the I-Ab subregion.…”
Section: Resultssupporting
confidence: 88%
“…Most of these experiments were performed at low temperatures, in the presence of sodium azide. The variable success of such experiments could be explained by the necessity of physiological temperature and metabolic energy for T cell antigen binding [31,321 and T cell stimulation [19,[33][34][35]. Similarly, difficulties in radioactive antigen suicide of helper cells were overcome by Basten et al, only when the cells were incubated at physiological temperature in the presence of adherent cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that in contrast to B cells, T cells bind antigen optimally at physiological temperature, and that binding could be inhibited by sodium azide [19,201. This suggested that antigen binding to T cells in partially purified cul-C 3 H.SW nylon wool-purified T cells were pretreated with MF and subsequently labeled with 12'I-labeled (T,G)-A--L for different periods of time.…”
Section: Characteristics Of Antigen Binding To Lyt-l+ T Cellsmentioning
confidence: 99%
“…
The role of surface immunoglobulin (Ig) in triggering B-lymphocyte responses is not yet clear. For several years it has been known that anti-Ig antibodies can interfere with the activation of B cells by mitogens (1)(2)(3)(4)(5). Whether this block is external, interfering with the mitogenic receptor, or internal, affecting deeper features of the cells' metabolism, is not yet established.Anti-Ig antibodies have a particularly deleterious effect on the immature B lymphocyte (6), suggesting that surface Ig may control the state of differentiation and activation of the B cell.
…”
mentioning
confidence: 99%